Pengembangan Alat Pembakar Sampah Portabel untuk Pengelolaan Sampah Mandiri - Ignatius Aris Hendaryanto; Budi Basuki; Andhi Akhmad Ismail; Dani Anggoro Hasan Hasan; Y. Bayu Triswantoko; Rudy Hermawan; Dany Setyawan; Hari Setiyo Utomo (Universitas Proklamasi 45, 2026)
Suboptimal household waste management remains a problem in various regions. Waste is generally disposed of in landfills (TPA) or burned openly, both of which have negative impacts on the environment. Open burning of waste produces air pollution in the form of carbon monoxide, dioxins, and fine particles that are harmful to health. Therefore, this study aims to design and manufacture a portable, smoke-free waste incinerator as an alternative solution for independent waste management. The research methods used include literature review, design using CAD software, component fabrication, tool assembly, and functional testing. This tool is designed with a combustion system in a furnace with controlled air flow to optimize the combustion process and reduce smoke emissions. The result of this study is a prototype of a portable waste incinerator that is easy to move. Based on the results of functional tests and visual observations, this waste incinerator can burn dry leaves, with the condition that there is still quite a lot of smoke at the beginning of the combustion and the smoke puffs are significantly reduced as the flame grows.